Long Non-Coding RNA and Breast Cancer. (19th July 2019) - Zhang, Tianzhu; Hu, Hui; Yan, Ge; Wu, Tangwei; Liu, Shuiyi; Chen, Weiqun; Ning, Yong; Lu, Zhongxin
Breast cancer, one of the most common diseases among women, is regarded as a heterogeneous and complicated disease that remains a major public health concern. Recently, owing to the development of next-generation sequencing technologies, long non-coding RNAs have received extensive attention. Numerous studies reveal that long non-coding RNAs are playing important roles in tumor development. Although the biological function and molecular mechanisms of long non-coding RNAs remain enigmatic, recent researchers have demonstrated that an array of long non-coding RNAs express abnormally in cancers, including breast cancer. Herein, we summarized the latest literature about long non-coding RNAs in breast cancer, with a particular focus on the multiple molecular roles of regulatory long non-coding RNAs that regulate cell proliferation, invasion, metastasis, and apoptosis.